(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, the history of the development of education for children with disabilities, its importance, the role of inclusion in preparing children with disabilities for social life, and the analysis of the results of a small research study conducted among students of a higher educational institution are highlighted.